Evaluation of bisbenzamidines as inhibitors for matriptase-2. Issue 15 (1st August 2016) - Beckmann, Anna-Madeleine; Gilberg, Erik; Gattner, Susanne; Huang, Tien L.; Vanden Eynde, Jean Jacques; Mayence, Annie; Bajorath, Jürgen; Stirnberg, Marit; Gütschow, Michael
Graphical abstract: Abstract: The serine protease matriptase-2 has attracted much attention as a potential target for the treatment of iron overload diseases. In this study, a series of 27 symmetric, achiral bisbenzamidines was evaluated for inhibitory activity against human matriptase-2, against the closely related enzyme human matriptase, as well as against human thrombin, bovine factor Xa and human trypsin. The conformationally restricted piperazine derivative19 and the oxamide-derived bisbenzamidine1 were identified as the most potent inhibitors of this series for matriptase-2 and matriptase, respectively.